Mechanism of immunosuppression in leprosy: presence of suppressor factor(s) from macrophages of lepromatous patients. - Salgame, P R (1983)
Human peripheral blood mononuclear cell proliferation induced by Mycobacterium leprae could be inhibited by the suppressor factor in the lysate of the macrophages of lepromatous leprosy patients. Macrophages from normal subjects and tuberculoid patients did not show production of a suppressor factor. Inhibition occurred only when the factor was present in the initial stages of lymphocyte culture. The factor is heat stable and nondialyzable. Proliferation induced by some mycobacteria and concanavalin A could also be blocked by the factor. Interestingly, blastogenic response by a few other antigens and phytohemagglutinin could not be inhibited by the suppressor factor. Mononuclear cells pretreated with such lysate from lepromatous macrophages for 24 h could induce suppressive activity in the cells in vitro in an autologous system. Treatment of these cells with carbonyl iron after the induction phase, to remove phagocytic cells, did not abolish their suppressive activity. The lepromatous macrophage lysate also generated suppressive activity in a T-lymphocyte-enriched population of normal subjects. These studies are interpreted to indicate that immunosuppression in lepromatous patients is produced by both macrophages and T lymphocytes. The exact phase in which either of these cells acts as a suppressor may be different. Specific suppression by macrophages to M. leprae can be an early event, and nonspecific suppression by T lymphocytes may be a later event in the course of lepromatous leprosy.